Bangladesh genocide and the issue of justice : papers presented in the International conference held at Heidelberg University, Germany, 4 - 5 July, 2013 - Hoque, Mofidul; Wara, Umme (Liberation War Museum, 2013)
Contributed papers, presented at a conference held at Heidelberg University, organized by South Asia Institute, Heidelberg University, South Asia Democratic Forum, Brussels, Belgium, Liberation War Museum, Bangladesh.